Service innovation in Philippine industries - Ramonette B. Serafica (Philippine Institute for Development Studies (PIDS), 2016)
This paper examines the evidence on service innovation using the 2012 Census of Philippine Business and Industry and the 2009 Pilot Survey of Innovation Activities. It reveals the wide variation in R and D intensities and differences in innovation behavior between the manufacturing and services sectors, for example, with respect to information sources and innovation activities. Many similarities were also detected in terms of service product innovation, the popularity of organizational innovation, and the preference for training activities, among others. Looking at structural factors, the probit regression analyses indicate that the size of the firm is a good determinant for all types of innovation. Ownership and age were also significant for certain innovation outputs, which could help inform policies on foreign direct investment and entrepreneurship. The results of this paper reveal the importance of service innovation not only for the services sector but also for the manufacturing sector consistent with servicification. In general, different types of innovation are undertaken by industries for various reasons, and the technological and nontechnological forms of innovation complement each other. If the government aims to promote economy-wide upgrading, support for innovation should not favor only one type of innovation output or activity. Further research on innovation behavior to cover more industries will be useful in developing a comprehensive and more nuanced approach to innovation policy.
Keywords: 330; innovation; services; manufacturing; R&D; servicification